2008
DOI: 10.1002/smll.200700804
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Single‐Layered Colloidal TiS2 Nanodisks

Abstract: Single‐layered titanium sulfide nanodisks (see image) are prepared for the first time using the wet chemical method. The size of the nanodisks are controlled by changing the experimental conditions. The synthesized nanodisks show interesting structural changes at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 58 publications
2
64
0
Order By: Relevance
“…Interestingly enough, the reproduction factors calculated for 1T‐MoS 2 →2H‐MoS 2 reactions are smaller and energy barriers are one order higher than those discovered for titanium disulfide TiS 2 (3.75 and 0.12 eV) . This can explain the fact that both 1T and 2H forms of MoS 2 are observed in experiments and both forms are quite stable in the absence of external impacts, while 2H form of TiS 2 is quite unstable and can be seen only in some specific conditions like colloidal nanodisks . Note also that 1T form is more stable in TiS 2 while 2H form is more stable in MoS 2 .…”
Section: Resultsmentioning
confidence: 78%
“…Interestingly enough, the reproduction factors calculated for 1T‐MoS 2 →2H‐MoS 2 reactions are smaller and energy barriers are one order higher than those discovered for titanium disulfide TiS 2 (3.75 and 0.12 eV) . This can explain the fact that both 1T and 2H forms of MoS 2 are observed in experiments and both forms are quite stable in the absence of external impacts, while 2H form of TiS 2 is quite unstable and can be seen only in some specific conditions like colloidal nanodisks . Note also that 1T form is more stable in TiS 2 while 2H form is more stable in MoS 2 .…”
Section: Resultsmentioning
confidence: 78%
“…Only kinetic reasons hinder its formation. 34 Previous theoretical calculations have shown that such 2D TiO 2 phase is metastable against various 3D forms, 35 but to our knowledge an isolated 2D-TiO 2 nanostructure has never been synthetized. Using a relatively large 6 × 6 supercell (and a grid of 4 × 4 k-points to sample the Brillouin zone) we have also evaluated the pairing energy between couples of O substituents.…”
Section: Tis 2 Monolayers: Structure and Thermodynamics Of Oxidationmentioning
confidence: 89%
“…Titanium Disulfide (TiS 2 ) is a metallic thermoelectric material which attains unique morphologies such as nanotubes, nanoclusters and nanodisks, and exhibits interesting physical properties. [187][188][189][190][191][192][193][194][195][196][197][198] Meng et al 199 has prepared 2D TiS 2 nanosheets decorated on graphene using a ball milling method and followed by high-temperature annealing. photoanode for a DSSC was prepared by immersing it in N719 dye solution for 24 hours at room temperature.…”
Section: Tis 2 Counter Electrodesmentioning
confidence: 99%